The financial determinants of corporate cash holding: Evidence among US, UK and China Markets - Tang, Chu Wah Bryan (2012)
This paper investigated firms’ cash holdings decisions by using firm- level data from US, UK and China with regard to different financial determinants and dummy variables, and the empirical results arising from my regression analysis may shed some lights as to why firms hold cash. All-in-all, cash holdings decisions of firms are mainly affected by leverage, firm size, cash flow to asset, debt maturity, country and industry-specific factors.